Transfer of Company’s Seat - an Unfolding Story in Europe - Frost, Carsten (Victoria University of Wellington Law Review, 2005)
The harmonisation of company law has long been a goal of the European Union. Questions concerning the freedom of establishment have always been both a central and controversial area of European law. The European Court of Justice has decided in favour of the freedom of establishment of EU companies establishing themselves in other Member States in several cases since Centros in 1999, resulting in a discernible and consistent line of authority. The Court has made clear that Member States have to allow companies that have been incorporated in other Member States to freely enter their territory, according to the rules under which they have been formed in their state of origin. But the decisions have left other important questions open to doubt. The purpose of this article is to examine the consequences of these judgments, not only for European company law, but for related legal areas as well. The paper addresses this issue by giving a short overview on the freedom of establishment under the Treaty Establishing the European Community and on the existing European theories about the transfer of a company’s seat. It then analyses the European Court of Justice cases and their implications. The article argues that the pressure on national legislators that arises from the judgments helps to keep European company law attractive to investors. It concludes that an increased mobility of companies within Europe is necessary if Europe is to remain competitive on an international level, even if the price of this is the abolition of some traditional domestic legal principles.